Total Quality Management (Tqm) Analysis Of Zakat At The Muhammadiyah Zakat, Infak, And Shadaqah Institution (Lazismu) In West Java Region, 2021 Period - Abdul Haris Suhadak; M. Sulaeman Jajuli (LP2M IAIN Palopo, 2025)
This study aims to analyze the implementation of Total Quality Management (TQM) in zakat management at the Muhammadiyah Zakat, Infaq, and Alms Institution (LAZISMU) in West Java, and its implications for improving service quality, muzakki trust, and the effectiveness of zakat fund utilization. The approach used is descriptive-qualitative with phenomenological analysis of primary and secondary data through documentation, observation, and interviews. The results show that the implementation of TQM at LAZISMU West Java includes three main aspects: strengthening the organizational management system, increasing the competence of amil resources, and digital-based service innovation. The principles of continuous improvement, customer focus, and employee involvement are applied contextually within the framework of sharia values, resulting in institutional governance that is accountable, professional, and oriented towards the welfare of the community. In addition, the implementation of TQM integrated with maqāṣid al-syarī'ah strengthens the social function of zakat as an instrument of economic justice and community empowerment. This integration places the spiritual and moral dimensions as part of the institution's quality system, so that zakat management not only produces organizational efficiency, but also contributes significantly to the objectives of sharia in safeguarding wealth (ḥifẓ al-māl), soul (ḥifẓ al-nafs), and reason (ḥifẓ al-'aql). This study confirms that TQM in zakat institutions can be a sustainable Islamic quality management model to strengthen public trust and the socio-economic effectiveness of Islamic philanthropic institutions in Indonesia